Does Greater Regulatory Burden Lead to More Corruption? Evidence Using Firm-Level Survey Data for Developing Countries - Amin, Mohammad (World Bank E-Library Archive, 2020)
Regulation often creates opportunities for public officials to extract bribes. If this is true, deregulation offers a simple way to combat corruption. However, empirical evidence on the corruption and regulation nexus is limited. Further, the corruption indices used are based on experts' opinions, which may suffer from perception bias. The present paper attempts to address these shortcomings using firm-level survey data for 131 mostly developing countries on the experiences of the firms with bribery and regulatory burden. Exploiting within-country and industry-level variation in regulatory burden, the analysis finds a large, positive effect of regulatory burden on corruption. For the baseline results, the bribery rate is higher by about 0.03 percentage point for each percentage point increase in the regulatory burden. The finding is robust to several endogeneity checks